IMPLEMENTASI METODE WATERFALL DALAM MEMBANGUN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMK NEGERI 1 ATAMBUA - Kolloh, Renaldi Yulvengki; Darsono Nababan; Risald (Politeknik Negeri Indramayu, 2024)
The library at SMK Negeri 1 Atambua still employs a conventional management system for tasks such as new member registration, book inventory recording, book lending, and others. This approach is, of course, lacking in supporting convenience and transaction effectiveness between library members and staff. Therefore, there is a need for a web-based library information system that can facilitate both students and teachers in accessing the library application as a provider of information and knowledge services. In developing this system, the waterfall methodology is employed. The library information system utilizes PHP programming and the Laravel framework, with MySQL as the database. The result of this research is a web-based library information system that can assist students, teachers, and library staff in better library management and administration compared to the previous conventional system.